Routine Preoperative Group Crossmatching and Postoperative Check Hemoglobin Is not Necessary in Patients Undergoing Total Knee Arthroplasty - Tay, Adriel You Wei; Thever, Yogen; Bin Abd Razak, Hamid Rahmatullah; Hao, Ying; Tan, Andrew Hwee Chye (The Journal of Knee Surgery, 2020)
This study aims to find out if routine preoperative group crossmatch and postoperative check hemoglobin for total knee arthroplasty (TKA) patients is necessary. A retrospective analysis was performed on patients who underwent unilateral TKAs for osteoarthritis from January 1, 2004 to December 31, 2014. The main outcome measures were postoperative hemoglobin levels and transfusion requirements. Patients' demographics, comorbidities, laboratory results, and surgical details were analyzed. A total of 955 TKAs were included in this study (males = 207, females = 748; mean age = 66.1 years, standard deviation [SD] = 7.7). A total of 79 (8.27%) cases required postoperative blood transfusion, and the crossmatch-transfusion ratio was 17.5. Significant predictors for postoperative transfusion included lower preoperative hemoglobin levels (p < 0.001) and advanced age (p < 0.001). Receiver operating characteristic (ROC) curve and Youden's Index analyses identified the preoperative hemoglobin cut-off value for females to be 12.1 g/dL (relative risk (RR): 5.65, p < 0.001) in predicting postoperative blood transfusion requirement, and 12.4 g/dL (RR: 11.71, p < 0.001) for males. For age, the identified cut-off value was 68 years (RR: 3.18, p < 0.001). The largest decline in hemoglobin levels was noted on postoperative day (POD) 3 (31.8%), and smallest on POD 1 (18.8%). The postoperative transfusion requirements in TKA are low and do not justify routine perioperative blood investigations. However, these investigations should be reserved for patients with the identified risk factors, in particular advancing age (68 years and above) and lower preoperative hemoglobin (below or equal to 12.1 and 12.4 g/dL for females and males, respectively). In the event that postoperative hemoglobin level needs to be checked, it should be performed beyond the first POD.
Keywords: knee arthroplasty; group crossmatch; transfusion; hemoglobin; risk factor